Kidney tubular injury of rats caused by unripe green betel nuts (Areca catechu) - Ave Olivia Rahman; Anati Purwakanthi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Unripe green betel nuts (Areca catechu) are usually consumed as herbal medicines by some inhabitants in several regions of Indonesia. It is considered that the nuts contain Arecoline hydrobromide that can cause damages in a kidney tubule, although it needs further studies about effects of the nuts.Objective: This study aims to determine the effects of the unripe green betel nuts on kidney tissues of rats in a long-term treatment.Methods: Twenty rats used in this study were Sprague-Dawley strain, male, 2-3 months old, and 150-200 gram of weight. They were randomly divided into four groups. Group I was control group, given distilled water once a day; group II, III, and IV were served by juice of the unripe green betel nuts with a dose of 250 mg/kgBW, 1,000 mg/kgBW, and 10,000 mg/kgBW, respectively. Histopathology examination by staining of Haematoxylin Eosin was conducted by an anatomic pathologist using blind methods including glomerulus, tubulus, and interstitial tissues.Result: The tested kidney tissues showed mild interstitial congestion, tubular cast, and tubular degeneration in groups that received unripe green betel nuts. There were no glomerulus abnormality and interstitial inflammation. The highest percentage of rats suffering injury in their kidney was the group IV, with p value <0.05 when compared to the control group.Conclusion: Long-term consumption of unripe green betel nuts could cause kidney tubular injury.